Internship and Monograph reports entitled ”Cell Membrane-Coated Nanosystems for Gene Delivery Applications" - Sequeira, Marta Baptista (2020)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia